Entrepreneurship, job creation, and growth in fast-growing firms in Portugal: is there a role for policy? - Sarmento, Elsa (2018)
Economies that thrive most on their ambitions, innovative and productive firms are due to grow and develop. Our motivation is thus to uncover who are these fast-growing firms and where they operate. These interrogations provide the foundation for an exploration into what are the different choices for policy, and an opportunity to engage afresh with why and if they ought to receive support in the first place, infusing the discussion as to when and how it could be provided and what could the intended results be. We use the dataset Quadros de Pessoal to provide a stronger twofold measurement, according to the employment and turnover growth criteria. We find among Portugal’s distinctive characteristics its high share of SMEs in the population of fast-growing firms, the narrowing down of the difference between measurements according to the employment and turnover criteria and the disproportionate amount of employment generated by the largest segment of fast-growing firms. We find that gazelles are outstanding job creators, having a disproportionately larger impact in job creation than high-growth firms. Accordingly, it is the rapid growth of a few large firms, combined with the entry of a higher number of firms of a higher average size that generates positive net job creation in Portugal. A more thorough understanding of fast-growing firms ought to lead to adjustments in government policies to heighten their exceptional contribution to economic growth. We provide a conceptual framework for tapping into how to design policies for firms which are growing at a faster pace and a roadmap for tackling some of its most controversial issues.